LEXICOGRAPHIC PROBLEMS IN MODERN DICTIONARIES - Alimnazarova , Nafisa; Robiya , Jorabekova (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article discusses the main problems of modern lexicography and dictionary compilation. It analyzes issues such as polysemy, homonymy, pronunciation difficulties, translation problems, neologisms, slang, and electronic dictionaries. The article also explains the importance of lexicography in language learning and communication. Modern technologies and corpus linguistics have improved dictionary making, but many challenges still remain.